Unusual sites of delayed metachronous metastases from renal cell carcinoma: a case series of five cases and review of literature - Singh, Anshuman; Chawla, Arun; Wali, Manjunath Irappa; Shah, Abhijit; Gali, Kasi Viswanath (International Journal of Research in Medical Sciences, 2023)
Renal cell carcinoma (RCC) is the most common malignant tumour of the kidney, representing 3% of all adult malignancies. Among men it is the sixth most common cancer while among women it is the ninth most common cancer. The mainstay of treatment for localized RCC is surgical resection with curative intent. The aggressive and often insidious nature of RCC is reflected by high recurrence rates of upto 20-40% after nephrectomy. Most commonly encountered sites of recurrent metastases include the lung, followed by bone, liver, brain, and local recurrence. Atypical sites of delayed metastases of RCC, although rare, have been reported in literature. We present our series of five cases where delayed metastasis has occurred at atypical sites including right sartorius muscle, right atrium and ventricle, urinary bladder, shaft of tibia and distal phalanx of hand upto six years later from the time of initial curative treatment of primary. The metastatic lesions in sartorius muscle, right atrium and ventricle, urinary bladder and distal phalanx were primarily managed by metastatectomy while that in the tibial shaft was managed by palliative targeted therapy with tyrosine kinase inhibitors. The key takeaway from this case series is that any primary neoplastic lesion in a patient with history of RCC should be evaluated with histopathology before definitive intervention is undertaken keeping in mind the notorious tendency of RCC to cause delayed metachronous metastases at unusual sites. In presence of solitary metastatic lesions at resectable locations, curative treatment can be offered by metastatectomy.